Whom should I call next? : New Finnish Comics. Kenelle soittaisin seuraavaksi? - Hänninen, Harto; Jaukkuri, Maaretta; Kemppinen, Petri (Helsinki : KIASMA Museum of Contemporary Art, 1999)
Björklund, Maria ; Eräsaari, Jenny ; Rantio, Grönroos & ; Hagelberg, Matti ; Haglund, Bo ; Kallio, Kaltsu ; Kallio, Pauli ; Kalliokoski, Marko ; Karjalainen, Jussi ; Kovács, Kati ; Laitinen, Karri ; Larmola, Kivi ; Lavonen, Anu ; Lindström, Christer ; Musturi, Tommi ; Nissen, Hans ; Numminen, Terhi ; Nuutinen, Christer ; Otsamo, Pentti ; Pynnönen, Ville ; Pystynen, Tilna ; Rapia, Kati ; Riionheimo, Tomi ; Roikonen, Jii ; Rojola, Johanna ; Rope, Jenni ; Rosse, Stéphane ; Tikkanen, Petteri ; Toivonen, Sami ; Tolppanen, Petri ; Tukiainen, Katja ; Tuomola, Juba ; Uusitalo, Riitta ; Valkeapää, Jukka-Pekka ; Vuori, Julia ; Väyrynen, Mikko
biografie
Whom should I call next? : New Finnish Comics, KIASMA Museum of Contemporary Art, Helsinki, 22.5. - 26.9.1999
Engels & Fins
boek